Responsible filmmaking: ethics and spectatorship through the lens of Michael Haneke - Weys, Daniël Jan (Centre for Film and Media Studies, 2017)
My dissertation uses, as starting point, an interview with Michael Haneke in which the Austrian filmmaker criticises Downfall and Schindler's List for manipulating audiences and for generating entertainment from real-life and unspeakable horrors. He argues that filmmakers have a responsibility to enable audiences to form their own opinion regarding a film and its subject matter. I set forth to engage, theorise and develop Haneke's call for responsibility by asking the following questions as I move chronologically through his films: why is responsible filmmaking important, how does Haneke approach his own filmmaking and how does a responsible approach to filmmaking influence the position of spectators. Firstly, I draw from Stanley Cavell's film theory to read our current experience in a media saturated society, describing the ways in which the media positions and influences the characters' understanding of the world and their relationships with each other in The Seventh Continent, Benny's Video and 71 Fragments of a Chronology of Chance. Thereafter, I discuss Haneke's use of genre in Funny Games, the long take and continuity editing in Code Unknown, music in The Piano Teacher and sound in Time of the Wolf to analyse Haneke's approach to filmmaking. My readings are underpinned by Cavell's understanding of automatism and the manner in which Haneke uses and reflects upon film's automatisms. Finally, I illustrate Levinas' concept of responsibility for the Other through a reading of Georges and Majid's relationship in Caché, Kelly Oliver's work on witnessing in The White Ribbon and Judith Butler's work on responsibility in Amour in order to demonstrate how Haneke's responsibility ensures the audience's response-ability.